Case Report: A rare case of hemorrhagic cystic IPAS masquerading as pancreatic neoplasm - Chen, Chong-yuan; Yang, Yu; Hu, Ming-zheng; Xing, Rong-chun (Frontiers in Oncology, 2025)
Intrapancreatic accessory spleen (IPAS) is a rare congenital developmental anomaly that is typically benign and does not require specific treatment. However, when IPAS undergoes hemorrhage and subsequent cystic degeneration, its clinical symptoms and laboratory findings often lack specificity, and imaging studies can be misleading, frequently resulting in misdiagnosis as pancreatic tumors or other lesions. This poses significant challenges for preoperative diagnosis. We report a case of a 53-year-old woman presenting with vague upper abdominal pain. Preoperative imaging strongly suggested a mucinous cystic neoplasm of the pancreas. However, postoperative pathology following laparoscopic distal pancreatectomy combined with splenectomy confirmed hemorrhagic cystic degeneration of an IPAS. This case highlights the importance of considering hemorrhagic cystic IPAS in the differential diagnosis of pancreatic space-occupying lesions, particularly when imaging findings are atypical or inconclusive. Endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) is a safe and effective method for obtaining a pathological diagnosis. Enhanced awareness of this condition, combined with meticulous radiological evaluation and necessary histopathological biopsy, can reduce misdiagnosis, avoid unnecessary surgical trauma, and improve individualized treatment strategies.